Prevalence of respiratory morbidity among brick kiln workers: a cross sectional study from rural north India - Gupta, Rushali; Gupta, Riya; Jan, Rayaz; Langer, Bhavna; Gupta, Rajiv K.; Singh, Parveen (International Journal of Research in Medical Sciences, 2019)
Background: Fired clay bricks, an important construction material, are manufactured in non-mechanized, labour intensive brick kilns which mostly employ unskilled men and women. The workers, as an occupational hazard, are exposed to dust and air pollution leading to respiratory diseases. Methods: This cross sectional study was conducted among brick kiln workers in RS Pura block of Jammu district. The workers were assessed regarding respiratory symptoms and illnesses using translated version of American Thoracic Society Division of Lung Disease questionnaire (ATS-DLD-78A). Results: 692 brick kiln workers were interviewed during the course of survey and 58.8%of them were males. 45% of the respondents were working since last less than three years. Among the respiratory symptoms chronic cough, was present in 23.55% and phlegm in 22.83% of the respondents. Chronic bronchitis was present in 20.52% of the respondents. Association of respiratory symptoms in relation to sex of the respondents was found to be statistically significant (p<0.05). Conclusions: Respiratory symptoms and illness were found to be quite prevalent in the brick kiln workers. More research needs to be conducted to assess other health risks besides respiratory morbidity. Health planners need to plan for their basic sanitation facilities and periodic check ups.